Upgrading China Pakistan Bilateral Relations through Everyday Life Communications: Cases from North Minzu University - Ma, Jianfu (Pacific International Journal, 2023)
What we know about the very good relations between China and Pakistan and the concrete implementation of the Belt and Road Initiative is only reported by the media of the two countries, rather than the personal experience of the people from both China and Pakistan. From the perspective of anthropology, in this article, authors suggested that the exchanges and interactions between two countries should be reflected in the concrete cultural exchanges. In recent years, we have invited scholars from Pakistan to China and carried out a variety of activities such as forums, lectures, seminars and conferences, in order to reinforce the mutual understandings between two countries. Afterwards, the evaluations and reflections from participants proved that these academic activities are meaningful to the concrete practice of the friendship between China and Pakistan.